Effect of substrate to filament distance on formation and photoluminescence properties of indium catalyzed silicon nanowires using hot-wire chemical vapor deposition - Chong, Su Kong; Goh, Boon Tong; Dee, Chang Fu; Rahman, Saadah Abdul (2013)
Si nanowires have been synthesized by hot-wire chemical vapor deposition technique, with Indium nanocones employed as catalysts with different substrate to filament distances ranging from 6 to 3 cm. Reducing the substrate to filament distance resulted in the retention of more atomic H radicals on the growth sites. The atomic H radicals acted to induce the catalytic growth and enhance the crystallinity of the Si nanowires. The Si nanowires showed tapering structures due to the radial growth of columnar Si nanocrystallites on the middle and base walls of the nanowires. The oxide-related defects on the outer layer of the Indium nanocones and Si nanowires, as well as the Si nanocrystallites on walls of the Si nanowires, contributed to the visible orange and red photoluminescence.